Persepsi Dokter Klinik Dalam Menggunakan Rekam Medis Elektronik Berbasis Cloud Computing: Survei Penggunaan rekmed.com - Emi Azmi Choironi; Lukman Heryawan (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
Background : The use of electronic medical records (EMR), including cloud computing-based EMR, is widely increasing. However, data regarding the perception of physicians using cloud computing-based EMR in Indonesia is still limited. Objective: This study aims to determine the perception of clinical doctors in using EMR based on cloud computing. Methods: This is a cross sectional study with a mixed-methods explanatory sequential design approach to determine the perception of clinicians in using cloud computing-based EMR. Qualitative analysis is used to support the depth of quantitative data analysis. Result: There are 10 private clinic doctors who participate. The average value of respondents' satisfaction after using cloud computing-based EMR is 7.4 from a scale of 1-10, with a median value of 8. In the analysis of interest in using cloud computing-based EMR in the long term, it was found that 30% of respondents said